If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15x + -4 + 4x + 5 + 65 = 0 Reorder the terms: -4 + 5 + 65 + 15x + 4x = 0 Combine like terms: -4 + 5 = 1 1 + 65 + 15x + 4x = 0 Combine like terms: 1 + 65 = 66 66 + 15x + 4x = 0 Combine like terms: 15x + 4x = 19x 66 + 19x = 0 Solving 66 + 19x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-66' to each side of the equation. 66 + -66 + 19x = 0 + -66 Combine like terms: 66 + -66 = 0 0 + 19x = 0 + -66 19x = 0 + -66 Combine like terms: 0 + -66 = -66 19x = -66 Divide each side by '19'. x = -3.473684211 Simplifying x = -3.473684211
| 7(b-4)=5(b-2) | | 2(3b-4)=5(b-1) | | 3(3a+1)=30 | | 4(1/3x-1/4)+4/3x/3+1=6 | | 8-4=6z-8z | | k^3+2k^2-10k-20=0 | | 7(x+2)=7x+10 | | z^4-26z^2+25=0 | | 5x-10-2=13 | | 1/2x16=0 | | p^(2/3)+p^(1/2) | | 3x-7+5=16 | | (x^2-81)/(x^2-6x-27)*(x+3)/x | | 98x+456= | | x^3-4x=85008 | | 250=(50-3)+x | | s=2x+t/r | | x/5-x=1/5 | | 0.5y=30 | | -6(x-2)+4(8x-12)=68 | | 6ln(3x)=12 | | -6(x-2)-4(8x-12)=68 | | 3x-2=7x+8 | | 4(-6+x)=5x+1/4 | | h=4a-3 | | 1/6-18/12 | | 7-3(5t-7)=67 | | 5x^2y^4-80x^4y^2=0 | | 1=23*t+2-1-2+1-23*t+2*t-1*t | | 23*t+2-1-2+1-23*t+2*t-1*t=1 | | 2w^2-5w-88=0 | | 2x-6+5=11 |